2001
DOI: 10.1128/aem.67.6.2571-2577.2001
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Disruption of the proBA Locus in Listeria monocytogenes : Role of Proline Biosynthesis in Salt Tolerance and Murine Infection

Abstract: Intracellular accumulation of the amino acid proline has previously been linked to the salt tolerance and virulence potential of a number of bacteria. Taking advantage of the proBA mutant Escherichia coli CSH26, we identified a listerial proBA operon coding for enzymes functionally similar to the glutamyl kinase (GK) and glutamylphosphate reductase (GPR) enzyme complex which catalyzes the first and second steps of proline biosynthesis in E. coli. The first gene of the operon, proB, is predicted to encode GK, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
1
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 54 publications
3
60
1
3
Order By: Relevance
“…The proline biosynthetic pathway encoded by the proAB genes catalyzes de novo synthesis of proline from intracellular pools of glutamate via gammaglutamyl kinase (proA) and gammaglutamyl phosphate reductase (proB). In the serotype 1/2c laboratory strain LO28, this pathway participates in osmotic protection in the absence of preferred osmoprotectants betaine and carnitine (53). Although both the microarray and southern blot data indicate that the proAB genes are absent in all lineage I strains that we tested, four different restriction fragment length polymorphism patterns were observed among the lineage II strains and three lineage II strains were missing the genes.…”
Section: Resultsmentioning
confidence: 81%
“…The proline biosynthetic pathway encoded by the proAB genes catalyzes de novo synthesis of proline from intracellular pools of glutamate via gammaglutamyl kinase (proA) and gammaglutamyl phosphate reductase (proB). In the serotype 1/2c laboratory strain LO28, this pathway participates in osmotic protection in the absence of preferred osmoprotectants betaine and carnitine (53). Although both the microarray and southern blot data indicate that the proAB genes are absent in all lineage I strains that we tested, four different restriction fragment length polymorphism patterns were observed among the lineage II strains and three lineage II strains were missing the genes.…”
Section: Resultsmentioning
confidence: 81%
“…Moreover, in vivo approaches have demonstrated that genes involved in arginine, biotin, and proline metabolism in Vibrio cholerae (7), E. coli (26) and Helicobacter pylori (25), respectively, are induced during mouse infection. In one of the closest relatives of L. plantarum, Listeria monocytogenes, proline metabolism is induced under high-osmolarity conditions (47). Such conditions could potentially be found in the colon and suggest differential colonic expression of lp0017 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Several of our microarray probe sequences have close BLASTx matches for proteins that might confer differential fitness in different food processing or natural environ- ments. These include a protein related to the repair of UV damage to the chromosome (probe 961), two proteins implicated in salt tolerance (probes 774 and 1085) (30), one gene related to exopolysaccharide synthesis (biofilm formation; probe 1094), and one heavy-metal transporter (probe 289). Additionally, probe 955 is most similar to beta-glucoside-specific enzyme II (bvrB) of the L. monocytogenes phosphotransferase system.…”
Section: Vol 41 2003 L Monocytogenes Genomics 635mentioning
confidence: 99%